Diversification brings prosperity - Singh, Ritu; Singh, Rashmi; Kumar, Rakesh (Indian Horticulture, 2015)
Kunal Gahlot is truly a torch bearer and percolates new concept, variety, package of practices and ideas among the farming fraternity in the Alipur block.